Reciprocal impacts of black rhino and community-based ecotourism in North-West Namibia - Beytell, Petrus Cecil (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Geography and Environmental Studies)--University of Stellenbosch, 2010.